2006
DOI: 10.3354/ame042215
|View full text |Cite
|
Sign up to set email alerts
|

Purine and pyrimidine metabolism by estuarine bacteria

Abstract: Nucleotide bases are ubiquitous in living organisms, but the fate of these compounds in natural environments is poorly understood. Here we studied the metabolism of selected purines and pyrimidines in estuarine bacterial assemblages from the Øresund, Denmark. Depletion of nucleotide bases in the incubations was followed by the appearance of urea. The purine guanine and the catabolic intermediates hypoxanthine and xanthine were depleted 2 times faster from seawater incubations than the purine adenine, and 8 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 32 publications
3
29
0
Order By: Relevance
“…Uric acid is further broken down into ureides such as allantoin and allantoic acid by the enzymes uricase, allantoinase, and allantoicase (allantoate amidinohydrolase), producing urea (Vogels & Van der Drift 1976, Garrett & Grisham 1995, Wang et al 2008). Interestingly, guanine appears to be more widely produced, leading to a higher availability, and therefore higher rates of uptake and catabolism, compared with adenine in the marine environment (Antia et al 1975, Shah & Syrett 1982, 1984, Berg & Jørgensen 2006. On the basis of sequence similarity, a putative purine transporter gene, AaURA, was discovered in Aureococcus anophagefferens and shown to be highly expressed during growth on a number of different N sources and under N-limited conditions (Berg et al 2008).…”
Section: The Urea Cycle and Purine Catabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…Uric acid is further broken down into ureides such as allantoin and allantoic acid by the enzymes uricase, allantoinase, and allantoicase (allantoate amidinohydrolase), producing urea (Vogels & Van der Drift 1976, Garrett & Grisham 1995, Wang et al 2008). Interestingly, guanine appears to be more widely produced, leading to a higher availability, and therefore higher rates of uptake and catabolism, compared with adenine in the marine environment (Antia et al 1975, Shah & Syrett 1982, 1984, Berg & Jørgensen 2006. On the basis of sequence similarity, a putative purine transporter gene, AaURA, was discovered in Aureococcus anophagefferens and shown to be highly expressed during growth on a number of different N sources and under N-limited conditions (Berg et al 2008).…”
Section: The Urea Cycle and Purine Catabolismmentioning
confidence: 99%
“…Among the natural sources of urea in the water column are regeneration by heterotrophic bacteria (Mitamura & Saijo 1981, Cho & Azam 1995, Cho et al 1996, Berg & Jørgensen 2006, excretion by macro-and microzooplankton (Corner & Newell 1967, Mayzaud 1973, Bidigare 1983, Miller & Glibert 1998, L'Helguen et al 2005, Miller & Roman 2008, Painter et al 2008, and release by phytoplankton (Hansell & Goering 1989, Bronk et al 1998, Bronk 2002. Urea is also produced by benthic heterotrophic bacteria and macrofauna and released from sediments into the water column (Lomstein et al 1989, Lund & Blackburn 1989, Pedersen et al 1993, Therkildsen et al 1997.…”
Section: Sources Of Urea To Aquatic Ecosystemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other nucleobases were detected at 4.58 min (5mC), 5.63 min (HX), and 5.89 min (X), respectively. The LOD concentrations for primary nucleobases ranged from 20-32 nmol L -1 (Table 1), and were comparable to or lower than those reported previously for HPLC and UPLC analyses (Berg and Jørgensen 2006;Fan et al 2007;Sotgia et al 2010;Tavazzi et al 2005). The LOQ concentrations ranged from 65 to 110 nmol L -1 .…”
Section: Hplc-dad Methods For Nucleobase Analysismentioning
confidence: 84%
“…We did not examine the suite of amino acids in the kelp-derived DON but did detect urea. While kelp itself is unlikely to release urea, microbial communities are likely to catabolise larger N compounds to urea (Berg & Jørgensen 2006). The ability of leaves to uptake DON derived directly or indirectly from kelp provides seagrass with a shortcut to bioavailable N directly from the N between seagrass leaves only and those with rhizome and roots in our experiment suggests that N can be taken up through both leaves and roots, which is supported by Vonk et al (2008) who demonstrated that both DIN and DON are taken up by seagrass leaves and roots.…”
Section: Subsidy Pathway To Primary Producersmentioning
confidence: 99%